Combinatorial effects of genistein and sex-steroids on the level of cystic fibrosis transmembrane regulator (CFTR), adenylate cyclase (AC) and cAMP in the cervix of ovariectomised rats - Salleh, N.; Ismail, N.; Muniandy, S.; Korla, P.K.; Giribabu, N. (2015)
The combinatorial effects of genistein and estrogen (E) or estrogen plus progesterone (E + P) on CFTR, AC and cAMP levels in cervix were investigated. Ovariectomised adult female rats received 50 or 100 mg/kg/day genistein with E or E followed by E + P [E + (E + P)] for seven consecutive days. Cervixes were harvested and analyzed for CFTR mRNA levels by Real-time PCR. Distribution of AC and CFTR proteins in endocervix were observed by immunohistochemistry. Levels of cAMP were measured by enzyme-immunoassay. Molecular docking predicted interaction between genistein and AC. Our results indicate that levels of CFTR, AC and CAMP in cervix of rats receiving genistein plus E were higher than E-only treatment (p < 0.05) while genistein plus [E + (E + P)] were higher than E + (E + P)-only treatment (p < 0.05). In conclusions, increased levels of CFTR, AC and cAMP in cervix of E and E + (E + P)-treated rats by genistein could affect the cervical secretory function which could influence the female reproductive processes. (C) 2015 Elsevier Inc. All rights reserved.